Pendidikan Akhlak Siswa Madrasah Ibtidaiyah: Konsep Dan Urgensinya Di Era Globalisasi - Sitti Aisya Tampilang; Paisal Rabuka; Nasrah Maidah Dalingsahe (Tamilis Synex: Multidimensional Collaboration, 2025)
The advancement of technology and science that has developed thoroughly has made an era of globalization full of sophistication in various sectors. The impact is immediately felt in various fields of human life not only in the material aspects of life, but continues in non-material aspects such as morals. The urgency of implementing moral development is carried out in the family, community and education environment. This research uses qualitative research methods using literature review techniques. The purpose of literature research is to gain a deep understanding of the material being explored. The result of the literature review is that character is an order that is firmly embedded in the soul from which various actions emerge easily and lightly, without requiring thought and consideration needed in the era of globalization. Learners, especially the Madrasah Ibtidaiyah level, need a strong moral foundation. and good morals. Like the opinion of AlGhazali and KH Mustofa Bisri.